Exporting 'The Cotter's Saturday Night': Robert Burns, Scottish Romantic Nationalism and Colonial Settler Identity. Issue 1 (April 2019) - Sharp, Sarah
Abstract : A Scottish literary icon of the nineteenth century, Burns's 'The Cotter's Saturday Night' was a key component of the cultural baggage carried by emigrant Scots seeking a new life abroad. The myth of the thrifty, humble and pious Scottish cottager is a recurrent figure in Scottish colonial writing whether that cottage is situated in the South African veld or the Otago bush. This article examines the way in which Burns's cotter informed the myth of the self-sufficient Scottish peasant in the poetry of John Barr and Thomas Pringle. It will argue that, just as 'The Cotter' could be used to reinforce a particular set of ideas about Scottish identity at home, Scottish settlers used Burns's poem to respond to and cement new identities abroad.